Students Problems in Completing Final Paper (Skripsi) - Tsani, Intan Ghifra; Amalia, Annisa Rizki; Hariadi, Lintang Vikhasri Putri; Purwanti, Eko (Universitas Muhammadiyah Yogyakarta, 2024)
A final paper or Skripsi is one of the mandatory requirements for a bachelor’s degree, it means that students have to fulfill their final paper in order to graduate from their study program. This paper aims to determine students' problems in completing their final paper (Skripsi). This research used a Qualitative approach with the Case Study as its design and method to gain information. The information of data is gathered through in depth-interviews with four respondents that mostly are currently working on their final papers and an alumnus. The results are divided into two types. From the external factor, the most frequent problem could be found related to the student's supervisor while the internal problems frequently concern the final paper Chapter 1, student’s motivation, and time management. Therefore, students were able to solve each of their obstacles by using their own strategies.